High emissions of greenhouse gases from grasslands on peat and other organic soils. (12th May 2016) - Tiemeyer, Bärbel; Albiac Borraz, Elisa; Augustin, Jürgen; Bechtold, Michel; Beetz, Sascha; Beyer, Colja; Drösler, Matthias; Ebli, Martin; Eickenscheidt, Tim; Fiedler, Sabine; Förster, Christoph; Freibauer, Annette; et al.
Abstract: Drainage has turned peatlands from a carbon sink into one of the world's largest greenhouse gas (GHG) sources from cultivated soils. We analyzed a unique data set (12 peatlands, 48 sites and 122 annual budgets) of mainly unpublished GHG emissions from grasslands on bog and fen peat as well as other soils rich in soil organic carbon (SOC) in Germany. Emissions and environmental variables were measured with identical methods. Site‐averaged GHG budgets were surprisingly variable (29.2 ± 17.4 t CO2 ‐eq. ha −1 yr −1 ) and partially higher than all published data and the IPCC default emission factors for GHG inventories. Generally, CO2 (27.7 ± 17.3 t CO2 ha −1 yr −1 ) dominated the GHG budget. Nitrous oxide (2.3 ± 2.4 kg N2 O‐N ha −1 yr −1 ) and methane emissions (30.8 ± 69.8 kg CH4 ‐C ha −1 yr −1 ) were lower than expected except for CH4 emissions from nutrient‐poor acidic sites. At single peatlands, CO2 emissions clearly increased with deeper mean water table depth (WTD), but there was no general dependency of CO2 on WTD for the complete data set. Thus, regionalization of CO2 emissions by WTD only will remain uncertain. WTD dynamics explained some of the differences between peatlands as sites which became very dry during summer showed lower emissions. We introduced the aerated nitrogen stock (Nair ) as a variable combining soil nitrogen stocks with WTD. CO2 increased with Nair across peatlands. Soils with comparatively low SOC concentrations showed as high CO2 emissions as true peat soils because Nair was similar. N2 O emissions were controlled by the WTD dynamics and the nitrogen content of the topsoil. CH4 emissions can be well described by WTD and ponding duration during summer. Our results can help both to improve GHG emission reporting and to prioritize and plan emission reduction measures for peat and similar soils at different scales.